Study guides

☆

More answers

Lvl 1

a x B

Still have questions?

Continue Learning about Other Math

2a + 4b

6b+5a-4b+3a= ? Rearrange it as 5a+3a+6b-4b = 8a+2b

2a + 3a + 4 = 5a + 4

2a + 5a + 3a = 10a

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].

Related questions

2a + 4b

6b+5a-4b+3a= ? Rearrange it as 5a+3a+6b-4b = 8a+2b

2a² + 6a

2a + 3a + 4 = 5a + 4

5a + 11

It is an algabraic expession without knowing whether or not 2b and 3a are plus or minus

2a + 3a = 5a

2a + 5a + 3a = 10a

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].

The given expression can be simplified to: 3b-a

a + 3a + 5a = 180 9a =180 a = 20

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

People also asked

Featured Questions